Promoting increased compliance of managing patients with bacterial vaginosis - О. В. Грищенко; И. В. Лахно (Publishing House TRILIST, 2017)
Bacterial vaginosis is a multiple infectious agents-associated epithelial pathology that captures local leukocyte reaction deficiency and the lack of humoral defense mechanisms of vaginal mucosa. The effective sanitation of vagina requires finding a combination of antiseptic substances that contribute to the destruction of the biofilm and improving the transport in the vaginal epithelium. The study was aimed to the investigation of the efficacy of vaginal suppositories containing chlorhexidine and dexpanthenol (Depanthol, Stada) usage for the treatment of patients with bacterial vaginosis. There were examined 142 patients of reproductive age who were divided into several clinical groups. In group I (control) 30 healthy women were included in the process of examination. In group II (comparison) 52 patients with bacterial vaginosis were monitored whom were administered metronidazole-containing vaginal suppositories once daily during the week. 60 women with bacterial vaginosis were enrolled in III (main) group those were treated with vaginal suppository Depanthol twice daily for 7 days. The data demonstrated that in patients with bacterial vaginosis the prevalence of gardnerella and atopobium alliance with aerobic and anaerobic microorganisms, yeasts andprotozoa was found. Depanthol effectively influenced pathogens contributing to the reestablishment of the functional properties of vaginal mucosa. This contributed to the eradication of the main symbionts of vaginal biofilm - Gardnerella vaginalis and Atopobium vaginae and almost excluded the repeated episodes within six months of observation in the main group. The RR of the recurrence was 8.1 in group II (95% CI 1.1-58.4, sensitivity - 93.3%, specificity - 43.3%), and in group III the RR was 1.0 (95% CI 1.0-10.6, sensitivity - 66.7%, and specificity - 33.3%).